Exploring the Instructional Value and Worth of a MOOC. (July 2015) - MacDonald, Patrick; Ahern, Terence C.
Technology offers new and innovative ways to deliver learning such as the Massive Open Online Courses (MOOCs). The MOOC offers institutes of higher education a potential delivery method for delivering online learning. This study utilized a qualitative method to gather and analyze an active observer's experience within a MOOC. The results aligned with the current literature, demonstrating that MOOCs have potential as an educational tool, but careful consideration should be placed in what a participant values and finds worthwhile. Findings indicate that creating a worthwhile experience includes consideration of time constraints, consistence in delivery, and audience analysis.